Au regard du sacré : lectures croisées de la médina de Fès - Brice Gruet (Itinéraires)
This paper focuses on the analysis of Fes medina, Morocco, through the work of Titus Burckhardt, Fes, city of Islam, published in the 1960s. The author emphasizes on the sacred aspects of the city and proposes a thoughtful investigation of the specific history of this urban space. Burckhardt provides us with a critical insight into Fes’ evolution within both a colonial and then postcolonial context. He praises the strength of muslim tradition, and especially the sufi one. This vision is confronted with nowadays Fes, the possibilities of development of the whole city and the contradictions of such a project.